UNIT 4C.2 Burkholderia thailandensis: Genetic Manipulation. Issue 1 (16th May 2017) - Garcia, Erin C.
Abstract : Burkholderia thailandensis is a Gram‐negative bacterium endemic to Southeast Asian and northern Australian soils. It is non‐pathogenic; therefore, it is commonly used as a model organism for the related human pathogens Burkholderia mallei and Burkholderia pseudomallei . B. thailandensis is relatively easily genetically manipulated and a variety of robust genetic tools can be used in this organism. This unit describes protocols for conjugation, natural transformation, mini‐Tn7 insertion, and allelic exchange in B. thailandensis . © 2017 by John Wiley & Sons, Inc.